Rave on : the biography of Buddy Holly - Norman, Philip, 1943- (New York : Simon & Schuster, 1996)
Draws on interviews with many of Holly's associates, as well as his widow, to create a portrait of the young man who took the American music scene by storm and then died in a tragic plane crash
Includes index.
Keywords: Holly, Buddy, -- 1936-1959.; Rock musicians -- United States -- Biography